Action of dwarf mucuna, pigeon pea and stylos anthes on weed under field and laboratory conditions - Rosa, Danielle Medina; Nóbrega, Lúcia Helena Pereira [UNESP]; De Lima, Gislaine Piccolo; Mauli, Márcia Maria; Coelho, Sílvia Renata MacHado (My University, 2011)
The quality and allelopathy properties of dwarf mucuna, dwarf pigeon pea and stylosanthes as cover crops on corn and weed species were evaluated. Seeds were sown in October 2007, with a control treatment, in 20 plots of 4×5m, with five replicates. Weed population was determined 30 and 60 days after sowing. At 90 days, plants were mowed and the residues left to remain on the plot. Fresh and dry mass of the cover crops were determined and the allelopathic potential of aqueous extract of their aerial part was tested. The extract was chemically characterized and applied on seeds of weeds and corn. The experimental design was completely randomized and averages compared by the Scott-Knott test at 5% significance. The cover crops showed to be effective in the control of weeds. The highest values in fresh and dry mass were obtained for dwarf pigeon pea, followed by dwarf mucuna; fresh mass increased 72 and 34%, respectively, compared to the control. The extract with dwarf mucuna affected arrowleaf sida germination. The use of green manure in the summer or between harvests ensures that crop rotation is carried out properly and warrants its benefits.